Non-covalent interactions in extended systems described by the effective fragment potential method: theory and application to nucleobase oligomers - Ghosh, Debashree; Kosenkov, Dmytro; Vanovschi, Vitalii; Williams, Christopher F.; Herbert, John M.; Gordon, Mark S.; Schmidt, Michael W.; Slipchenko, Lyudmila V.; Krylov, Anna I. (Journal of Physical Chemistry A, 2010)
The implementation of the effective fragment potential (EFP) method within the Q-CHEM electronic structure package is presented. The EFP method is used to study noncovalent π-π and hydrogen-bonding interactions in DNA strands. Since EFP is a computationally inexpensive alternative to high-level ab initio calculations, it is possible to go beyond the dimers of nucleic acid bases and to investigate the asymptotic behavior of different components of the total interaction energy. The calculations demonstrated that the dispersion energy is a leading component in π-stacked oligomers of all sizes. Exchange-repulsion energy also plays an important role. The contribution of polarization is small in these systems, whereas the magnitude of electrostatics varies. Pairwise fragment interactions (i.e., the sum of dimer binding energies) were found to be a good approximation for the oligomer energy.